Duodenal ulcer penetration into the superior mesenteric artery after percutaneous transluminal angioplasty and stent placement for acute mesenteric ischemia: report of a case - Ouchi, Akira (Springer Japan, 2013)
A 78-year-old male presented with the chief complaints of abdominal pain and vomiting. Contrast-enhanced computed tomography and abdominal angiography showed occlusion of the superior mesenteric artery due to thrombosis, and emergency percutaneous transluminal angioplasty and stent placement were carried out. Two months later, stent thrombosis developed, and a second stent was placed. Eight months later, he complained of general fatigue and anorexia. Gastrointestinal endoscopy revealed a duodenal ulcer at the third portion close to the superior mesenteric artery. Thirteen days after conservative management, duodenal ulcer penetration into the superior mesenteric artery with subsequent air embolism developed, and the patient died of multiple organ failure.